Mix time affects diet uniformity and growth performance of nursery and finishing pigs - Traylor, S.L.; Behnke, Keith C.; Stark, C.R.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments were conducted to determine the effects of mix time on diet uniformity and growth performance of nursery and finishing pigs. For Exp. 1, 120 weanling pigs (average initial body wt of 12.1 lb) were used in a 27-d growth assay. The same Phase I diet (pelleted) was fed to all pigs for 7 d postweaning, then the pigs were switched to Phase II diet treatments for d 7 to 27. Treatments were mixing times of 0, .5, 2, and 4 min per 1,000 lb batch of complete feed in a double-ribbon mixer. From d 7 to 27, ADG increased by 49% and F/G was improved by 19% as mixing was increased from 0 to 4 min, with most of this effect realized with mixing for only .5 min (Le., a CV for diet uniformity of 28%). For Exp. 2, 128 finishing pigs (average initial body wt of 124 Ib) were fed to an average slaughter wt of 259 lb. All pigs were fed the same corn-soybean meal-based diet not mixed (0 min) or mixed for .5, 2, or 4 min per 1,000 lb batch of complete feed in a double-ribbon mixer. Increasing mix time (Le., reducing the CV for diet uniformity from 54% to <10%) did not significantly affect ADG, ADFI, or F/G. However, pigs fed the omin treatment had, numerically, the poorest rates and efficiencies of gain. Dressing percentage, backfat thickness, and bone strength were not affected by the dietary treatments. In conclusion, the difference in degree of response to diet uniformity for nursery vs finishing pigs probably was due to reduced palatability resulting from uneven [Department of Grain Science and Industry. 171 distribution of specialty ingredients in poorly mixed nursery diets (e.g., whey, blood meal, and crystalline amino acids). Also, the lower daily food intake of nursery pigs (1.5 Ib/d) vs finishing pigs (6.4 Ib/d) would decrease the likelihood of weanling pigs meeting their needs for some of the nutrients in a poorly mixed diet.
Keywords: Swine; Mixing; Diet uniformity; Growth; Bones; Nursery; Finishing